A stochastic model of eye lens growth. (7th July 2015) - Šikić, Hrvoje; Shi, Yanrong; Lubura, Snježana; Bassnett, Steven
Abstract: The size and shape of the ocular lens must be controlled with precision if light is to be focused sharply on the retina. The lifelong growth of the lens depends on the production of cells in the anterior epithelium. At the lens equator, epithelial cells differentiate into fiber cells, which are added to the surface of the existing fiber cell mass, increasing its volume and area. We developed a stochastic model relating the rates of cell proliferation and death in various regions of the lens epithelium to deposition of fiber cells and radial lens growth. Epithelial population dynamics were modeled as a branching process with emigration and immigration between proliferative zones. Numerical simulations were in agreement with empirical measurements and demonstrated that, operating within the strict confines of lens geometry, a stochastic growth engine can produce the smooth and precise growth necessary for lens function. Highlights: A stochastic model of lens growth is presented. Lens cell division is determined by proliferative fields associated with the lens surface. Numerical simulations are in accordance with empirical data sets. Surface areas of individual cells constrain the proliferative population and limit lens growth rate. Precise and reproducible radial growth can be generated using a stochastic growth engine.